P561 A comparison of medication adherence and persistence between intravenous biologics and oral small-molecule therapies. (16th January 2018) - Kane, S; Moran, K; Null, K; Huang, Z; Lissoos, T
Abstract: Background: Vedolizumab (VDZ) is approved for IBD as an intravenous (IV) infusion. However, new oral small molecule therapies such as tofacitinib (TOF), indicated for rheumatoid arthritis (RA), are currently being investigated in IBD. We examined adherence and persistence metrics of IV VDZ and oral TOF in RA and IBD. To better characterise the comparison between VDZ and TOF, we also examined infliximab (IFX), an IV biologic indicated for IBD and RA. Methods: We performed a retrospective cohort study using the Truven Marketscan ® database to compare adherence and persistence in adult IBD or RA patients (pts) who initiated VDZ or TOF between 1/1/2015 and 12/31/2015, as well as to IFX. Adherence over 12 months of follow-up was assessed as mean proportion of days covered (PDC) and cumulative days with gap ≥20% beyond the expected interval (CG20). The difference in PDC and CG20 between VDZ and TOF was estimated using multivariable generalised equation models. Persistence was assessed as time to treatment discontinuation over 12 months of follow-up using Kaplan–Meier survival analysis; the proportion of persistent patients was determined using a multivariable logistic regression model. Results: A total of 457 VDZ/IBD, 901 IFX/IBD, 378 IFX/RA, and 898 TOF/RApatients were analysed. Mean PDC was statistically higher in VDZ/IBD (77.71%) than in TOF/RA (68.22%; p ˂ 0.0001) (Table 1). PDC for VDZ/IBD was 4.66% higher than the projected PDC for TOF/IBD ( p = 0.0376). Mean CG20 was 67.35 in VDZ/IBD and 98.61 in TOF/RA and statistically different ( p ˂ 0.0001). Mean PDC and CG20 in IFX/RA were significantly higher than in TOF/RA but were similar between VDZ/IBD and IFX/IBD (Table 1). The proportion of persistent patients in VDZ/IBD was significantly higher than in TOF/RA ( p = 0.0001), and time to discontinuation was significantly shorter in TOF/RA than in VDZ/IBD ( p = 0.0012) and in IFX/RA ( p = 0.0044) (Table 1). Conclusions: Although limited by indirect comparisons, adherence and persistence were consistently higher with VDZ than with TOF. Previous studies have demonstrated that oral IBD therapies may be associated with reduced adherence. The decision to treat with oral therapy may be impacted by lower adherence and its effect on overall efficacy. Acknowledgment: We thank Yaping Wang, Charlie Cao, and Michelle Luo (Takeda Pharmaceuticals USA, Inc.) for help with analyses. This study and medical writing assistance (by Stephanie Agbu, PhD, of inVentiv Medical Communications) were supported by Takeda Pharmaceuticals USA, Inc.